The FOMO-Excitement Nexus: A Strategic Framework for Understanding Gen Z’s Impulsive Online Behavior - Misbah, Hanim; Sadeli, Fairuz Hazwani binti (CV. Bimbingan Belajar Assyfa, 2026)
The rapid proliferation of digital commerce strategies has intensified impulsive buying tendencies among Generation Z, yet the underlying psychological mechanisms remain complex. This conceptual paper develops an integrated framework to explain how digitally mediated engagement strategies intensify impulsive consumption. Grounded in the Stimulus–Organism–Response (S-O-R) model, this study identifies four salient digital stimuli: influencer marketing, gamification features, limited-time promotions, and user-generated content. It further posits that the affective states of 'fear of missing out' (FOMO) and 'excitement' serve as the primary mechanisms translating these stimuli into impulsive purchase behavior. Through a comprehensive analysis, the study suggests that while urgency-based cues amplify perceived scarcity, authenticity-based cues drive emotional arousal. The findings imply that while this study focuses on consumer behavior, the identified FOMO-Excitement nexus offers critical insights for educators to design more engaging, interactive, and ethically-minded instructional environments that better capture the attention of Gen Z learners. Consequently, this strategic framework provides a foundation for developing instructional media that aligns with the psychological drivers of contemporary digital natives, bridging the gap between commercial engagement tactics and pedagogical innovation in modern learning ecosystems.